Pertanggungjawaban Pidana Pencemaran Nama Baik Pejabat Pemerintah Melalui Media Sosial - Sherlyana Carmelita Tey Bhera; Retno Dewi Pulung Sari (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2023)
Defamation is a form of evil associated with dishonour and a person's good name. As the digital era of libel proliferates, the result of this development, many people suffer, even government officials. This study uses a legal-normative research method. Data collection was carried out by means of a literature study on related legal materials and analyzed descriptively. The results of the research show Indonesian legislation to protect an Indonesian person's honour and the good name was regulated under section 19 of 2016 to change section number 11 of 2008 in article 27 about information and electronic transaction (3). The criminal defamation applies to the delicht in article 45 (5) so that only victims can report. The complaint applies to all citizens, both civil and government officials. Article 45 of verse (3) arranges a criminal form of liability. Criminal liability includes criminal prison threats and criminal penalties.